Multifocal Analysis of Acute Pain After Third Molar Removal - Weckwerth, Giovana Maria; Dionísio, Thiago José; Costa, Yuri Martins; Zupelari-Gonçalves, Paulo; Oliveira, Gabriela Moraes; Torres, Elza Araújo; Bonjardim, Leonardo Rigoldi; Faria, Flavio Augusto Cardoso; Calvo, Adriana Maria; Moore, Troy; Absher, Devin Michael; Santos, Carlos Ferreira (Frontiers in Pharmacology, 2021)
Background: To analyze the pain modulation capacity profile in a Brazilian population, the relationship between opioid receptor (OPRM1) and Catechol-O-methyltransferase (COMT) polymorphisms and pain modulation capacity was determined through preoperative pain modulation tests and acute postoperative pain control evaluation, swelling, and trismus in 200 volunteers undergoing lower third molar. Methods: Psychologic and clinical parameters were measured. Patient DNA was sequenced for single nucleotide polymorphisms in OPRM1 and COMT, and the salivary concentration of interleukin (IL)-2, (IL)-6, interferon (IFN)- and tumor necrosis factor (TNF)- was evaluated. Primary outcomes were the influence of all predictors on the fluctuation of pain intensity using a visual analogue scale (VAS), and swelling and trismus on the 2nd and 7th postoperative days. Preoperative pain modulation capacity (CPM), pain catastrophizing scale (PCS), body mass index (BMI), and surgery duration and difficulty were evaluated. Results: Salivary concentration of IFN- and IL-2 as well as the duration of surgery influenced the fluctuation of postoperative pain in the VAS, and in the sum of the differences in pain intensity test at 8, 48, and 96 h. BMI influenced swelling, while both BMI and COMT haplotype influenced trismus on the 2nd postoperative day. Conclusions: Polymorphisms in COMT, salivary concentrations of IL-2 and IFN-, BMI, and duration of surgery were predictors for pain fluctuation, swelling, and trismus on the 2nd day after lower third molar extraction. This therapy was effective in controlling inflammatory symptomatology after lower third molar extraction and ibuprofen was well tolerated by patients.